2017
DOI: 10.1002/symb.305
|View full text |Cite
|
Sign up to set email alerts
|

“If I Can Offer You Some Advice”: Rapport and Data Collection in Interviews Between Adults of Different Ages

Abstract: Reflexively analyzing interactions between myself (young adult woman) and 150 adult research participants, I explore how interviewees responded to the interviewer's perceived age in combination with other social identity categories. Addressing a gap in scholarship on adult-adult interview interactions, this article examines how age gradations, in combination with other axes of similarity or difference, affect researcher-interviewee rapport and data acquisition. Racial similarity, regardless of age, unlocked ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…I believe my "insider status" (Collins, 1991) of having an immigrant family background, Latina identity, and my ties to the CSU were factors that helped me garner trust with participants who otherwise could have been hesitant to share their experiences. Recognizing that age gradations among adults matter, I believe my proximity in age to my interview respondents also helped provide a rapport (Vasquez-Tokos, 2017). Similar to the rapport reported in Enriquez's (2015) study, I, too, found a level of trustworthiness among interviewees as evidenced by their volunteering of sensitive information pertaining to illegal activity, abuse, and emotional feelings of regret, shame, and guilt.…”
Section: Methodssupporting
confidence: 56%
“…I believe my "insider status" (Collins, 1991) of having an immigrant family background, Latina identity, and my ties to the CSU were factors that helped me garner trust with participants who otherwise could have been hesitant to share their experiences. Recognizing that age gradations among adults matter, I believe my proximity in age to my interview respondents also helped provide a rapport (Vasquez-Tokos, 2017). Similar to the rapport reported in Enriquez's (2015) study, I, too, found a level of trustworthiness among interviewees as evidenced by their volunteering of sensitive information pertaining to illegal activity, abuse, and emotional feelings of regret, shame, and guilt.…”
Section: Methodssupporting
confidence: 56%
“…Do you feel that you have experienced racial/ethnic discrimination (If yes, could you describe the situation)? My positionality as a Latina woman likely facilitated access to interviews due to shared racial status (Vasquez-Tokos 2017b). Bearing light skin, dark hair, a Hispanic surname, and a research interest in race, I believe I am read as someone to whom recollections of racial discrimination could be safely surrendered.…”
Section: Methodology and Field Sitesmentioning
confidence: 99%
“…Perceptions about race and other embodied characteristics shape the interview process and may influence how respondents discuss racial matters (Gallagher 2003;Vasquez-Tokos 2017). Because I am a light-skinned, multiracial person with Southeast Asian and white European ancestry, respondents may have coded my race in a variety of ways.…”
Section: Methods and Sitementioning
confidence: 99%